2021
DOI: 10.1016/j.jcot.2021.05.019
|View full text |Cite
|
Sign up to set email alerts
|

Re-tears after rotator cuff repair: Current concepts review

Abstract: Re-tear following rotator cuff repair is common and has been reported to range from between 13 and 94% despite satisfactory clinical outcomes following rotator cuff surgery. Various risk factors have been associated with an increased tear rate, including patient factors, tear and shoulder morphology, repair technique, and rehabilitation regimes. Different modes of rotator cuff failure have been described. The management of re-tear in patients following rotator cuff repair is challenging and depends on the age,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 60 publications
(73 reference statements)
0
12
0
Order By: Relevance
“…The goal of conservative management is to restore range of motion and strengthen the residual intact rotator cuff, deltoid, and periscapular muscles. 10 This is achieved through rest, therapy, ice, anti-inflammatory medications, and possibly corticosteroid injections. Although the natural history of an untreated retear is progression of fatty degeneration and muscle atrophy, older and lower demand patients are often satisfied with their shoulder function and will not require surgical intervention.…”
Section: Non-operative Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…The goal of conservative management is to restore range of motion and strengthen the residual intact rotator cuff, deltoid, and periscapular muscles. 10 This is achieved through rest, therapy, ice, anti-inflammatory medications, and possibly corticosteroid injections. Although the natural history of an untreated retear is progression of fatty degeneration and muscle atrophy, older and lower demand patients are often satisfied with their shoulder function and will not require surgical intervention.…”
Section: Non-operative Managementmentioning
confidence: 99%
“…51 However, the tendon is not long enough to reach the humeral head and thus must be lengthened with addition of an allograft (Achilles) or autograft (IT band). 10,19,51 Most patients who undergo lower trapezius transfer with Achilles allograft report significantly improved pain, range of motion, and outcome scores at mean follow-up between 14 and 47 months. [52][53][54] Over half of the patients in each of these studies had previously undergone rotator cuff repair; however, direct comparisons between primary and revision cuff surgeries were not performed.…”
Section: Tendon Transfersmentioning
confidence: 99%
“…Despite the advancements in procedures for repair, re-tear of the repaired tendon is one of the most common complications encountered post-operatively [ 10 ]. Re-tear rates range between 13% and 94% of cases [ 11 ]. Some studies have suggested that patients who have a re-tear following repair surgery frequently still have a significant recovery in comparison with their preoperative state.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, failed repair and re-tear following RCT repair are major concerns for orthopedic surgeons. Retear rate after RCT repair has been reported to range up to 40% for small-to-medium tears and up to 94% for large and chronic tears [16][17][18]. Despite a large amount of literature on the management of RCTs and with the advancements in the technologies for RCT repair, surgical indications are not standardized.…”
Section: Introductionmentioning
confidence: 99%